HUBUNGAN PARITAS DENGAN PENGETAHUAN IBU NIFAS TENTANG PERAWATAN TALI PUSAT DI PUSKESMAS BAAMANG I SAMPIT TAHUN 2019 - Norwidya Priansiska (Journal of Midwifery and Reproduction, 2020)
The World Health Organization (WHO) found the number of infant deaths at 560,000, which is caused by infection of the umbilicalcord. Mothers who lack knowledge in teating the cord, causing the mother to usetraditional medicine clostridium tetanithus enabling the development of which can cause to infant mortality a baby. Types of quantitative analytic research. Cross sectional research design. The total of respondents as a sample of 20 postpartum. Data collection technique with accidental sampling and data analysis using univariate analysis and bivariate analysis. The result of univariate analysis showed that the majority of parity correctly as much as 10 postpartum (50%) , then knowledge the majority correctly as much as 13 postpartum (65%) . From bivariate analysis shows that there is a relationship between parity with postpartum knowledge about the umbilical cord carebecause ρ value < 0,05 (ρ value = 0,034).